Kidney Tubular Biomarkers in Type 1 Diabetes - Longitudinal Analysis of 2 Cohorts - Christine P. Limonte; David K. Prince; Andrew N. Hoofnagle; Irl B. Hirsch; Sushrut S. Waikar; Alessandro Doria; Michael Mauer; Bryan R. Kestenbaum; Ian H. de Boer (Kidney International Reports)
Introduction: Kidney tubular biomarker trends may provide insight into tubulointerstitial pathology that is not evident through measurement of glomerular filtration rate (GFR) and albumin excretion rate (AER). Methods: We examined longitudinal changes in tubular biomarkers in 2 type 1 diabetes (T1D) cohorts, namely the Renin-Angiotensin System Study (RASS, n = 283), including adults with normal GFR and AER and the Preventing Early Renal Loss in Diabetes Study (PERL, n = 530), including adults with albuminuria and/or rapid loss of estimated GFR (eGFR). The measurements included plasma kidney injury molecule-1 (KIM-1), soluble tumor necrosis factor receptor 1 (sTNFR1), arginine-citrulline ratio, urine epidermal growth factor (EGF), uromodulin (UMOD), and a tubular secretion score reflecting urinary clearances of 8 proximal tubular secreted molecules. Results: At baseline, RASS participants’ mean age was 30 years and 47% were male, with mean diabetes duration of 11 years, hemoglobin A1c (HbA1c) of 8.6%, iohexol-based measured GFR (iGFR) of 128 ml/min per 1.73 m2, and AER of 6 μg/min. PERL participants’ mean age was 51 years and 66% were male, with mean diabetes duration of 35 years, HbA1c of 8.2%, iGFR of 68 ml/min per 1.73 m2, and AER of 285 μg/min. Tubular biomarkers changed significantly over time as follows: KIM-1 of +5.7 pg/ml/yr, sTNFR1 of +14.2 pg/ml/yr, arginine-citrulline ratio of −0.03 units/yr, and EGF of −0.30 μg/d/yr in RASS; KIM-1 of +7.5 pg/ml/yr, sTNFR1 of +75.0 pg/ml/yr, UMOD of −3.4 mg/d/yr, and tubular secretion score of −0.53 units/yr in PERL. Higher baseline HbA1c and AER were associated with more rapid worsening of select tubular biomarkers in both RASS and PERL. Conclusion: Tubular biomarkers significantly worsen over time in T1D, potentially reflecting progression of tubulointerstitial pathology.